(untitled) (Third Sector Social Economic Review, 2026)
Economic complexity, which reflects the structures that retain and integrate knowledge, expressed in the composition of a country’s productive output, which is a measure of the amount of productive knowledge generated by society through its social interaction network, is sustainable as the country develops its ability to create and produce complex products by building complex capabilities, thus becoming the driving force of economic growth. The aim of this study is to analyze the effect of economic complexity on economic growth for 35 developing countries using annual data covering the period 1995-2022 with a panel ARDL (Autoregressive Distributed Lag) model. The analysis results show that all coefficients are statistically significant in both the long run and the short run. In the long run, fixed capital formation and goods and services exports have a positive effect on economic growth, while economic complexity has a negative effect. It can be argued that the negative relationship between the level of economic complexity and economic growth, which is contrary to expectations, is due to the fact that the factors constituting economic complexity are insufficient, not fully established, immature, and underdeveloped in developing countries. In developing countries, the institutional infrastructure that will enable progress in structural transformation, an organized social structure that facilitates communication, and science-based, long-term, continuous and sustainable systems must be strengthened and developed to increase the level of economic complexity and contribute to economic growth.